Incidence, antimicrobial resistance and mortality of Pseudomonas aeruginosa bloodstream infections among hospitalized patients in China: a retrospective observational multicenter cohort study from 2017 to 2021 - Xiao, Shuzhen; Liang, Xianghui; Han, Lizhong; Zhao, Shengyuan (Frontiers in Public Health, 2024)
Background: Pseudomonas aeruginosa (P. aeruginosa) accounts for high antimicrobial resistance and mortality rates of bloodstream infections (BSIs). We aim to investigate incidence, antimicrobial resistance and risk factors for mortality of P. aeruginosa BSIs among inpatients.Methods: A retrospective cohort study were conducted at two tertiary hospitals in 2017-2021. Medical and laboratory records of all inpatients diagnosed with P. aeruginosa BSIs were reviewed. A generalised linear mixed model was used to identify risk factors for mortality.Results: A total of 285 patients with P. aeruginosa BSIs were identified. Incidence of P. aeruginosa BSIs fluctuated between 2.37 and 3.51 per 100,000 patient-days over the study period. Out of 285 P. aeruginosa isolates, 97 (34.04%) were carbapenemresistant (CR) and 75 (26.32%) were multidrug-resistant (MDR). These isolates showed low resistance to aminoglycosides (9.51-11.62%), broad-spectrum cephalosporins (17.19-17.61%), fluoroquinolones (17.25-19.43%) and polymyxin B (1.69%). The crude 30-day mortality rate was 17.89% (51/285). Healthcare costs of patients with MDR/CR isolates were significantly higher than those of patients with non-MDR/CR isolates (P<0.001/=0.002). Inappropriate definitive therapy [adjusted odds ratio (aOR) 4.47, 95% confidence interval (95%CI) 1.35-14.77; P=0.014], ICU stay (aOR 2.89, 95%CI 1.26-6.63; P=0.012) and corticosteroids use (aOR 2.89, 95%CI 1.31-6.41; P=0.009) were independently associated with 30-day mortality.Conclusion: Incidence of P. aeruginosa BSIs showed an upward trend during 2017-2020 but dropped in 2021. MDR/CR P. aeruginosa BSIs are associated with higher healthcare costs. Awareness is required that patients with inappropriate definitive antimicrobial therapy, ICU stay and corticosteroids use are at higher risk of death from P. aeruginosa BSIs.